Childhood Asthma in Saudi Arabia: Insights from a Meta-Analysis on Its Prevalence - Abdullah Alzayed (Children)
A comprehensive review and meta-analysis were conducted with the purpose of determining the extent to which asthma is prevalent among children in Saudi Arabia. This was done with the intention of addressing the dearth of data at the national level regarding this significant health concern. The study included data from PubMed, Embase, Cochrane Library, and Google Scholar for the period 2015–2024, focusing on studies that reported the prevalence of asthma among children in the country. The primary outcome was the pooled prevalence of physician-diagnosed asthma among children. Eight studies, comprising a total of 9454 children, were included in the analysis. The estimated pooled prevalence of asthma was 28.9%, with a higher prevalence observed among boys compared to girls. A random-effects model was used to account for heterogeneity among studies, which was notably high (I2 = 99%). Factors contributing to the high prevalence included increasing urbanization, air pollution, and specific environmental exposures, particularly in regions like Jazan. Limitations of the analysis included reliance on self-reported data without spirometric confirmation and potential publication bias. Despite these challenges, the findings emphasize the urgent need for public health interventions to reduce asthma prevalence and improve outcomes. Future research should incorporate standardized diagnostic methods and objective measurements to provide more accurate estimates and to develop effective management strategies.